Selective Solid‐Liquid Interface Sulfidation Growth of Hierarchical Copper Sulfide and Its Hybrid Nanoflakes for Superior Lithium‐Ion Storage. Issue 11 (30th April 2020) - Zhang, Qiao; Ding, Ying; Huang, Aoming; Xu, Feng; Wang, Xueyou; Wang, Qingqing; Lin, Huijuan; Rui, Kun; Yan, Yan; Shen, Yu; Zhou, Yanping; Zhu, Jixin
Abstract: Two‐dimensional metal sulfides and their hybrids are emerging as promising candidates in various areas. Yet, it remains challenging to synthesize high‐quality 2D metal sulfides and their hybrids, especially iso‐component hybrids, in a simple and controllable way. In this work, a low‐temperature selective solid‐liquid sulfidation growth method has been developed for the synthesis of CuS nanoflakes and their hybrids. CuS nanoflakes of about 20 nm thickness and co‐component hybrids CuOx /CuS with variable composition ratios derived from different sulfidation time are obtained after the residual sulfur removal. Besides, benefiting from the mild low‐temperature sulfidation conditions, selective sulfidation is realized between Cu and Fe to yield iso‐component FeOx /CuS 2D nanoflakes of about 10–20 nm thickness, whose composition ratio is readily tunable by controlling the precursor. The as‐synthesized FeOx /CuS nanoflakes demonstrate superior lithium storage performance (i. e., 707 mAh g −1 at 500 mA g −1 and 627 mAh g −1 at 1000 mA g −1 after 450 cycles) when tested as anode materials in LIBs owing to the advantages of the ultrathin 2D nanostructure as well as the lithiation volumetric strain self‐reconstruction effect of the co‐existing two phases during charging/discharging processes. Abstract : A low‐temperature selective solid‐liquid sulfidation growth method was developed for the synthesis of CuS nanoflakes and their hybrids including co‐component CuOx /CuS and 2D iso‐component FeOx /CuS with variable composition ratios by tuning the sulfidation time or the precursor composition and the as‐obtained CuS and FeOx /CuS nanoflakes exhibited superior lithium storage performance.Insert text for Table of Contents here.